Tests of a Compton imaging prototype in a monoenergetic 4.44 MeV photon field—a benchmark setup for prompt gamma-ray imaging devices. (14th June 2016) - Golnik, C.; Bemmerer, D.; Enghardt, W.; Fiedler, F.; Hueso-González, F.; Pausch, G.; Römer, K.; Rohling, H.; Schöne, S.; Wagner, L.; Kormoll, T.
Abstract: The finite range of a proton beam in tissue opens new vistas for the delivery of a highly conformal dose distribution in radiotherapy. However, the actual particle range, and therefore the accurate dose deposition, is sensitive to the tissue composition in the proton path. Range uncertainties, resulting from limited knowledge of this tissue composition or positioning errors, are accounted for in the form of safety margins. Thus, the unverified particle range constrains the principle benefit of proton therapy. Detecting prompt γ -rays, a side product of proton-tissue interaction, aims at an on-line and non-invasive monitoring of the particle range, and therefore towards exploiting the potential of proton therapy. Compton imaging of the spatial prompt γ -ray emission is a promising measurement approach. Prompt γ -rays exhibit emission energies of several MeV. Hence, common radioactive sources cannot provide the energy range a prompt γ -ray imaging device must be designed for. In this work a benchmark measurement-setup for the production of a localized, monoenergetic 4.44 MeV γ -ray source is introduced. At the Tandetron accelerator at the HZDR, the proton-capture resonance reaction 15 N(p, α γ4.439 ) 12 C is utilized. This reaction provides the same nuclear de-excitation (and γ -ray emission) occurrent as an intense prompt γ -ray line in proton therapy. The emission yield is quantitatively described. A two-stage Compton imaging device, dedicated for prompt γ -ray imaging, is tested at the setup exemplarily. Besides successful imaging tests, the detection efficiency of the prototype at 4.44 MeV is derived from the measured data. Combining this efficiency with the emission yield for prompt γ -rays, the number of valid Compton events, induced by γ -rays in the energy region around 4.44 MeV, is estimated for the prototype being implemented in a therapeutic treatment scenario. As a consequence, the detection efficiency turns out to be a key parameter for prompt γ -rays Compton imaging limiting the applicability of the prototype in its current realization.